An Ecological and Societal Approach to Biological Control - EILENBERG, J.; HOKKANEN, H.M.T.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Biological control is among the most promising methods for control of pests (including vectors), diseases and weeds. In this book ecological and societal aspects are for the first time treated together. In an ecological approach the aim is to evaluate the significance of certain biological properties like biodiversity and natural habitats. Also, it is important to see biological control from an organic (or ecological) farming point of view. In a societal approach terms like 'consumer's attitude', 'risk perception', 'learning and education' and 'value triangle' are recognised as significant for biological production and human welfare.
CONCEPTS AND VISIONS OF BIOLOGICAL CONTROL -- SOCIOECONOMIC SIGNIFICANCE OF BIOLOGICAL CONTROL -- BIOLOGICAL CONTROL IN ORGANIC PRODUCTION: FIRST CHOICE OR LAST OPTION ? -- FOOD CONSUMPTION, RISK PERCEPTION AND ALTERNATIVE PRODUCTION TECHNOLOGIES -- EDUCATION IN BIOLOGICAL CONTROL AT THE UNIVERSITY LEVEL AT KVL -- IMPLEMENTATION OF BIOCONTROL AND IPM IN DUTCH HORTICULTURE -- BIOCONTROL IN PROTECTED CROPS: IS LACK OF BIODIVERSITY A LIMITING FACTOR? -- THE SOIL AS A RESERVOIR FOR ANTAGONISTS TO PLANT DISEASES -- THE SOIL AS A RESERVOIR FOR NATURAL ENEMIES OF PEST INSECTS AND MITES WITH EMPHASIS ON FUNGI AND NEMATODES -- DEGENERATION OF ENTOMOGENOUS FUNGI -- BIOLOGICAL CONTROL OF MOSQUITOES: MANAGEMENT OF THE UPPER RHINE MOSQUITO POPULATION AS A MODEL PROGRAMME -- BIOLOGICAL CONTROL OF SCARABS AND WEEVILS IN CHRISTMAS TREES AND GREENERY PLANTATIONS -- AN INTEGRATED APPROACH TO BIOLOGICAL CONTROL OF PLANT DISEASES AND WEEDS IN EUROPE -- POTENTIAL HEALTH PROBLEMS DUE TO EXPOSURE IN HANDLING AND USING BIOLOGICAL CONTROL AGENTS -- HARMONIA AXYRIDIS: A SUCCESSFUL BIOCONTROL AGENT OR AN INVASIVE THREAT?.
Keywords: LIFE SCIENCES; ECOLOGY; BOTANY; PLANT DISEASES; ENTOMOLOGY; LIFE SCIENCES; ENTOMOLOGY; PLANT PATHOLOGY; ECOLOGY; PLANT SCIENCES